Legal Education in Nigeria: Content, Methodology and Practice - Oyakhiromen, Ifidon (West African Journal of Open and Flexible Learning, 2026)
This paper seeks to showcase the methodology and practice of legal education in Nigeria in the face of globalisation and the trans-nationalisation of legal education. It considers the objectives of enacting the Legal Education Act, basic course content, methodology, practice, admission criteria and other components of legal education in Nigeria. It also outlines the benefits and burden of legal education in its present closed or open systems of education, and how globalisation and the revolution in information and communications technology affect legal education in Nigeria. It also examines the benefits of inter and intra-university partnerships and alliances between home universities and universities in other jurisdictions; and how far this has resulted in capacity building and skills transfer in legal education. Another issue it addresses is the limited capacity of the six Nigerian Law School Campuses across the federation with inadequate ICT and network systems, libraries and requisite training facilities, which has resulted in a backlog of prospective students.
Keywords: Legal education; ordinances